Observation of Equipment and Personal Protective Equipment in The Biology Laboratory - Putri, Desi Az Zahra; Erfin, Erfin; Paulus, Mira; Putri, Mega Julia; Sari, Siska Nilam; Sulaeman, Nurul Fitriyah (Vidya Karya, 2024)
This observation aimed to understand the laboratory regulations, assess the availability of Personal Protective Equipment (PPE) in the laboratory, evaluate management practices, examine the completeness of laboratory equipment and materials, and observe the arrangement of laboratory space, equipment, and materials. This research was conducted in the basic biology laboratory at a university in East Kalimantan. The method employed in this research involved interviewing laboratory assistants and observing the laboratory conditions. The observations indicated that Laboratory A and B had complete personal protective equipment. However, there were some differences. For instance, the equipment and materials were complete in Laboratory A, whereas in Laboratory B, they were incomplete because the laboratory was newly built. Another difference was in the usage of the laboratories; Laboratory A was used for practical sessions, seminars, and classroom activities, while Laboratory B was solely utilized for practical exams. For future researchers, it is suggested that laboratories be explored for both practical sessions and classroom activities, rather than just classroom spaces.